STUDENT AND TEACHER RESPOND ON APPLYING THE ENGLISH READING INSTRUCTION MATERIALS INTEGRATED INTO CHARACTER VALUES THROUGH SCIENTIFIC APPROACH (A PRACTICALITY STUDY IN MA.KM.M PADANG PANJANG) - Beniario, Beniario; Istiqa Sari, Istiqa Sari (FKIP UMSB, 2018)
Research studies on student and teacher respond on English reading instruction materials development integrated into character values and used in English learning process has increased several attention stated workshop, seminar and dissemination. In Indonesia, those studies have little attention as a development research base. Gusmaizal (2016), Beniario (2018) some studies relating with applying the instruction materials design is indicated as a practicality of instruction process activities. It infers with student and teacher respond during applying the English reading instruction materials design. This research was held at grade XI of MA KM.M Padang Panjang. Collecting data used questionnaires. The participants of the research were the students and teacher. The students respond was very practical and the teacher respond was practical in applying the English reading instruction materials integrated into character values through the scientific approach. To sum up, the implementing English instruction materials development was practical. This research development is strongly recommended for the English teachers in teaching English integrated into character values through scientific approach.Keywords: Reading, Character, Scientifik Approach